EL ESTADO DE DERECHO Y LA “SOCIEDAD DE RESTRICCIÓN” EN TIEMPOS DE PANDEMIA - Gonzales Pichihua, Markoni (2020)
The coronavirus pandemic is the origin of the implementation of exceptional regimes in several states around the world. The exceptional regime is part of the structure of liberal democracy and is legitimized by the rule of law. In these periods the “republican monarch” extends its powers and centralizes others. Exceptional legislation is produced, arbitrary legal sources are activated and the law of necessity is developed. In this time of exception, the rule of law continues to rule, but loses effectiveness, just as the state is still subject to the rule of law, but begins to make its arbitrary institutions visible. The only counterweight to the extensión of state power, in these circumstances, is the regime of capital, especially in the international arena. This article explains the “society of restriction” that develops at the heart of constitutional-pluralist regimes, both in ordinary periods and in crisis.